LUMAN/CREB3 Plays a Dual Role in Stress Responses as a Cofactor of the Glucocorticoid Receptor and a Regulator of Secretion - Penney, Jenna; Taylor, Tiegh; MacLusky, Neil; Lu, Ray (Frontiers in Molecular Neuroscience, 2018)
LUMAN/CREB3, originally identified through its interaction with a cell cycle regulator HCFC1, is a transcription factor involved in the unfolded protein response during endoplasmic reticulum stress. Previously using gene knockout mouse models, we have shown that LUMAN modulates the glucocorticoid (GC) response leading to enhanced glucocorticoid receptor (GR) activity and lower circulating GC levels. Consequently, the stress response is dysregulated, leading to a blunted stress response in the Luman-deficient mice. One question that remained was how LUMAN deficiency affected the stress response at the cellular level leading to the changes in the physiological stress response. Here, we found that LUMAN interacts with GR through a putative nuclear receptor box site and can activate GR in the absence of a ligand. Further investigation showed that, when activated, LUMAN binds to the glucocorticoid response element (GRE), increasing the activity of GR exponentially compared to GR-ligand binding alone. On the other hand, we also found that in the absence of LUMAN, cells were more sensitive to cellular stress, exhibiting decreased secretory capacity. Hence our current data suggest that LUMAN may function both as a transcriptional cofactor of GR and a hormone secretion regulator, and through this, plays a role in stress sensitivity and reactivity to stress.